Experiências de leitura de leitores jovens de uma escola pública de Cuiabá Mato Grosso - Leite, Rosana Campos (2007)
The present dissertation deals with the relation between reading and young readers from first years in a secondary public school located in Cuiabá-MT. So the investigation about reading practice and reading gesture means the central focus to examine the experience and tastes related to the reading act. A brief revision of literature was made, in witch the mainly those philosophers were study in a significant way focused or at least deal with, even in an indirect way, the reading and reading practice purpose. The research was guided by the following questions: What is the place and the meaning of reading experiences to each person? Which reading practice characterize the youth teenagers? What do young people think about their reading experiences? How is universe from de young reader according to the reading practice evidenced from other time? For it, we developed a chapter dedicated to the history of youth from the teenagers who lived in Greece until up to day. The following chapter tried to show the concept of reader and his way of reading. This research was done in Cuiabá and during a school bimester were collected informations though the interviews with questionnaire and subjective open questions trying to show readers and their readings in the youth. Even though living today a routine that insist in restate the difficulty to find a young reader or a reader student, and especially close to the literature and the books, we can note that reading experiences from each one are significant. The youth readings carry, so, an essential reference to the adult reader education. We intend with this work research to check the reading practice that the young follow in their lives. Practices that happen between the spaces from the school or particular situation and private reading show us a little about their readings choices. These readings are evidently by delighted situations, distraction and escape from the present. But it is shows and developed by an obligation way and the homework present on the school routine.